2015
DOI: 10.1007/s10518-015-9814-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil–structure interaction (structure-to-soil relative stiffness and mass ratio) on the fundamental period of buildings: experimental observation and analytical verification

Abstract: In order to investigate the influence of soil-structure interaction (SSI) on the dynamic characteristics of buildings, a series of free-vibration experiments were performed on a 1/4-scale steel-frame structure. The structural fixed-base fundamental period was for the first time determined by experiments as to avoid evaluation errors in the conventional SSI analyses, and its numerical counterpart obtained by using SAP2000 Ò was also given for comparison. A total of 34 scenarios, which varied with regard to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The results of their studies showed that the type of foundation is a major contributor to the seismic response of buildings with SSI. Xiong et al [4] investigated the influence of SSI on the dynamic characteristics of buildings. They carried out a series of free-vibration experiments on a scale-steel-frame structure.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their studies showed that the type of foundation is a major contributor to the seismic response of buildings with SSI. Xiong et al [4] investigated the influence of SSI on the dynamic characteristics of buildings. They carried out a series of free-vibration experiments on a scale-steel-frame structure.…”
Section: Introductionmentioning
confidence: 99%
“…As in many studies [16][17][18], it has been observed that the period of the structure increases in the acceptance of the SSI. Similarly, in this study, it has been observed that the building period increases in the SSI solutions (Figure 5).…”
Section: Research Resultsmentioning
confidence: 62%
“…In addition, Ref. [20] investigated the effects of SSI with series of free-vibration experiments on a 1/4-scale steel-frame structure by reproducing 34 scenarios under fixed-base and flexible-base conditions. Moreover, Ref.…”
Section: Introductionmentioning
confidence: 99%